Analyzing the Relationship Between Regeneration of Historic Centers and Urban Development Catalysts Case Study: Old Texture of Kermanshah - hamed baniamerian; alireza andalib; laala jahanshahloo (تحقیقات کاربردی علوم جغرافیایی)
Urban regeneration as a comprehensive approach to the restoration of historic centers, despite maintaining the main features of the space seeks to improve all the qualities of historic sites and tries to motivate development drivers in the process of historical reconstruction.  The aim of this study was to identify the most effective components of regeneration stimulating the development of historical centers following the adaptation of relationships between criteria on the historical core of Kermanshah.  The method of data analysis in this study is quantitative and the components of the theoretical framework in the form of a researcher-made questionnaire with closed questions, subject to validation of experts in the old context of Kermanshah (15 people in a purposeful and accessible way)  Is located.  The reliability of the questionnaire was evaluated using Cronbach's alpha method and SPSS software and the value was /76.  It is a sign of acceptable level of reliability.  Also, the adaptation of the components to the studied texture was plotted in the form of two decision trees with the help of Rapid Miner software, and the importance rank of the components was extracted.  The results show that the central core of the historical context of Kermanshah, due to the high volume of physical destruction, requires the formation of new construction while developing infrastructure, and the main existing functions require the reproduction of historical identity.  It also seems necessary to inject the flag project in combination with the development of accesses and local area network infrastructure in order to change the mood of the place.  Another result is that development drivers should define and refine the role of the historical core in the city as a whole and connect it as a development driver to the surrounding context in an interconnected network.  The results of applying the conceptual model of the research to the historical core of Kermanshah, confirm that the main criteria of the model are to a large extent applicable to the historical center of Iranian cities.